Resistance Training Combined With Cognitive Training Increases Brain Derived Neurotrophic Factor and Improves Cognitive Function in Healthy Older Adults - Castaño, Luz Albany Arcila; Castillo de Lima, Vivian; Barbieri, João Francisco; Lucena, Erick Guilherme Peixoto de; Gáspari, Arthur Fernandes; Arai, Hidenori; Teixeira, Camila Vieira Ligo; Coelho-Júnior, Hélio José; Uchida, Marco Carlos (Frontiers in Psychology, 2022)
Background The present study compared the effects of a traditional resistance training (TRT) and resistance training combined with cognitive task (RT + CT) on body composition, physical performance, cognitive function, and plasma brain-derived neurotrophic factor (BNDF) levels in older adults. Methods Thirty community-dwelling older adults were randomized into TRT (70.0 ± 8.1; 25% men) and RT + CT (66.3 ± 4.6; 31% men). Exercise groups performed a similar resistance training (RT) program, twice a week over 16 weeks. Cognitive Training involved performing verbal fluency simultaneously with RT. Exercise sessions (eight resistance exercises) were performed 2–3 sets, 8–15 repetitions at 60%–70% of 1-repetition maximum (1RM). Body composition, physical function, cognitive performance, and BDNF levels were assessed before and after intervention period. Results The physical performance was similarly improved in response to both TRT and RT + CT (p = 0.001). However, exclusive improvements on cognitive function (p < 0.001) and BDNF levels (p = 0.001) were observed only after RT + CT. Conclusion The RT program associated with a cognitive task, improved physical and cognitive performance in healthy older adults.